Diversity and ethics in trauma and acute care surgery teams: results from an international survey - Lorenzo Cobianchi; Francesca Dal Mas; Maurizio Massaro; Walter Biffl; Fausto Catena; Federico Coccolini; Beatrice Dionigi; Paolo Dionigi; Salomone Di Saverio; Paola Fugazzola; Yoram Kluger; Ari Leppäniemi; et al. (BMC, 2024)
Indexed by WOS